What Impacts do OER Have on Students? Students Share Their Experiences with a Health Psychology OER at New York City College of Technology - Cooney, Cailean (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
This article reports findings from a study conducted with students in three sections of a Health Psychology course that replaced a traditional textbook with open educational resources (OER) as the primary course material. The purpose of the study was to learn how OER impacted students. Data were collected in Fall 2015 with students from New York City College of Technology (City Tech), of the City University of New York (CUNY), a comprehensive college located in Brooklyn. Students were assigned the OER by their course instructor, who developed it as part of a library funded OER pilot initiative. Two research instruments were employed: one-on-one interviews and short surveys. Both interview and survey items asked students about how they engaged with the OER as their primary assigned course material. They shared feedback about the overall organization of the OER, ease of use, methods used to access the OER and complete coursework, benefits and challenges, and differences and similarities to using a traditional print textbook. Findings indicate that most students were able to access the OER more easily than traditional textbooks and responded positively to the variety of learning materials and assignments the OER assembled. Most students reported that course readings were equal to or better than traditional textbooks and would be willing to register for a course offering a similar resource in the future. A small amount of students reported minor usability issues. Also, few students had difficulties obtaining technology necessary to access the OER.